Gastrointestinal symptoms in COVID-19 - Lewandowski, Konrad; Kaniewska, Magdalena; Rosołowski, Mariusz; Rydzewska, Grażyna (Gastroenterology Review/Przegląd Gastroenterologiczny, 2023)
SARS-CoV-2 infection manifests mainly by involving the respiratory system. Due to the presence of abdominal symptoms, the digestive system is clearly involved in the expression, transmission, and possible pathogenesis of COVID-19. There are many theories regarding the development of abdominal symptoms, including angiotensin 2 receptor, cytokine storm, and disturbances of the intestinal microbiome. This paper provides an overview of the most important meta-analyses and publications on gastrointestinal symptoms and the gut microbiome in COVID-19.